2021
DOI: 10.1016/j.amsu.2021.102439
|View full text |Cite
|
Sign up to set email alerts
|

Does more testing in routine preoperative evaluation benefit the orthopedic patient? Case control study from a resource-constrained setting

Abstract: Background Routine preoperative tests in healthy patients not only cause extra anxiety, but may delay treatment without influencing surgical plan. This has worse impact in resource-constrained settings where fee for service rather than health insurance is the usual norm. Investigators aim to determine if “routine” pre-operative tests are justified in healthy orthopedic patients. Methods We conducted a non-commercialized, non-funded matched case control study in tertiary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Literature review regarding complete blood count (CBC) revealed that some of the available studies had tested individual components of CBC, that is, haemoglobin or haematocrit, total and differential leukocyte count and platelet count, while others had tested CBC as a whole. [ 3 11 12 13 19 20 21 22 23 24 ]…”
Section: Guidelines and Recommendationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Literature review regarding complete blood count (CBC) revealed that some of the available studies had tested individual components of CBC, that is, haemoglobin or haematocrit, total and differential leukocyte count and platelet count, while others had tested CBC as a whole. [ 3 11 12 13 19 20 21 22 23 24 ]…”
Section: Guidelines and Recommendationsmentioning
confidence: 99%
“…Anaemia is a global health issue with a prevalence rate of approximately 14% in ASA PS 1 and 2 preoperative patients. [ 3 11 12 13 19 20 21 22 23 24 25 26 27 ] This can contribute to adverse events such as tachycardia, arrhythmias, increased risk of infection, heart failure in the perioperative period. It can also contribute to increased duration of hospital stay, rates of intensive care admission and blood transfusion, which carry their own associated risks.…”
Section: Guidelines and Recommendationsmentioning
confidence: 99%
See 3 more Smart Citations